2022
DOI: 10.3389/fphar.2022.839790
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Development of Drug Delivery Systems Based on Small Extracellular Vesicles for Therapy of Brain Diseases

Abstract: Small extracellular vesicles (sEVs) have ∼30–200 nm diameter size and may act as carriers of different cargoes, depending on the cell of origin or on the physiological/pathological condition. As endogenous nanovesicles, sEVs are important in intercellular communication and have many of the desirable features of an ideal drug delivery system. sEVs are naturally biocompatible, with superior targeting capability, safety profile, nanometric size, and can be loaded with both lipophilic and hydrophilic agents. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 216 publications
(305 reference statements)
0
21
0
Order By: Relevance
“…Recently, more and more studies have focused on the enrichment of plasma exosomes into microglia ( Fitzner et al, 2011 ; Ginini et al, 2022 ; Loch-Neckel et al, 2022 ). Microglia, resident immune cells in the brain, engulf dead cells and help clear out misfolded aggregates of proteins, such as amyloid plaques in AD.…”
Section: The Role Of Exosomes In the Treatment Of Alzheimer’s Diseasementioning
confidence: 99%
“…Recently, more and more studies have focused on the enrichment of plasma exosomes into microglia ( Fitzner et al, 2011 ; Ginini et al, 2022 ; Loch-Neckel et al, 2022 ). Microglia, resident immune cells in the brain, engulf dead cells and help clear out misfolded aggregates of proteins, such as amyloid plaques in AD.…”
Section: The Role Of Exosomes In the Treatment Of Alzheimer’s Diseasementioning
confidence: 99%
“…Many studies have shown that EVs are transported over the BBB and reach the periphery; however, the underlying mechanism remains unclear, and evidence is sparse (Pegtel et al, 2014 ; Yáñez-Mó et al, 2015 ; Saint-Pol et al, 2020 ). Recent studies have shown that anti-inflammatory drugs could be delivered to the mice's brains through intranasal injection of EVs, indicating that EV administration to the CNS is feasible (Zhuang et al, 2011 ; Loch-Neckel et al, 2022 ). Similarly, the systemic administration has also exploited EVs to transfer small-interfering RNA molecules to mice brains (Cooper et al, 2014 ).…”
Section: Role Of the Blood–brain Barrier In The Transportation Of Evs...mentioning
confidence: 99%
“…Oncologists increase the total yield of sEVs by intracellular calcium production, external stress, cytoskeletal blocking, drug stimulation and the induction of gene expression factors. Furthermore, sEVs usually represent heterogeneous populations from different cell sources, and no standard separation process has been established to date to achieve product consistency (181); ii) the efficient incorporation of external antitumor agents and molecules is another demanding challenge that needs to be optimized. The high drug-loading content in sEVs must be sufficient to obtain a therapeutic response.…”
Section: Dleu2 and Afpmentioning
confidence: 99%